A discovery and selection protocol for decentralised cloudlet systems. (24th March 2023) - Parmar, Dilay; Joshi, Padmaja; Rao, Udai Pratap; Kumar, A. Sathish; Nivangune, Ashwin
Cloudlets help in overcoming latency issue of clouds in mobile cloud computing to offload the computing tasks. Communication protocols are important part of the implementation of cloudlet-based systems for the mobile-cloudlet-cloud environment. In this work, an approach for communication between entities in a decentralised cloudlet-based system is proposed. For that purpose, a cloudlet discovery protocol which is used for discovering cloudlets in Wi-Fi vicinity of mobile devices is proposed. A selection algorithm for selecting the suitable cloudlet from available discovered cloudlets is also proposed. Our proposed selection algorithm uses infrastructure specific criterion for selection decision, which makes the algorithm more generic to use.